Epidermal growth factor receptor signalling contributes to osteoblastic stromal cell proliferation, osteoclastogenesis and disease progression in giant cell tumour of bone. - Balla, P; Moskovszky, L; Sapi, Z; Forsyth, R; Knowles, H; Athanasou, N; Szendroi, M; Kopper, L; Rajnai, H; Pinter, F; Petak, I; Benassi, MS; et al. (2011)
AIMS: Epidermal growth factor receptor (EGFR) is implicated in bone remodelling. The aim was to determine whether EGFR protein expression contributes to the aggressiveness and recurrence potential of giant cell tumour of bone (GCTB), an osteolytic primary bone tumour that can exhibit markedly variable clinical behaviour. METHODS AND RESULTS: Immunohistochemical analysis on tissue microarrays (TMA) of 231 primary, 97 recurrent, 17 metastatic and 26 malignant GCTBs was performed using TMA analysis software and whole digital slides allowing validated scoring. EGFR expression was restricted to neoplastic stromal cells and was significantly more frequent in recurrent (71 of 92; 77%) than in non-recurrent GCTBs (86 of 162; 53%) (P = 0.002); and in clinicoradiologically aggressive (31 of 43; 72%) than latent (27 of 54; 50%) cases (P = 0.034). Detecting phosphotyrosine epitopes pY1068 and -pY1173 indicated active EGFR signalling, and finding EGFR ligands EGF and transforming growth factor-α restricted to cells of the monocytic lineage suggested paracrine EGFR activation in stromal cells. In functional studies EGF supported proliferation of GCTB stromal cells, and the addition of EGF and macrophage-colony stimulating factor promoted osteoclastogenesis. CONCLUSION: In GCTB, EGFR signalling in neoplastic stromal cells may contribute to disease progression through promoting stromal cell proliferation and osteoclastogenesis.